Life-Cycle-Based Multicriteria Sustainability Evaluation of Industrial Parks: A Case Study in China - Jin Yang; Bin Chen; Jing Qi; Shiyi Zhou; Meiming Jiang (The Scientific World Journal)
Along with increasing concerns on environmental protection and global warming mitigation, new industrial organization modes such as “Ecoindustrial Park” and “Low Carbon Industrial Park” are emerging. Since ecoindustrial parks and low carbon industrial parks may offer multifaceted benefits to the users, it naturally follows that the sustainability assessment of the industrial parks ought to adopt a multicriteria methodology. In this paper, a multicriteria sustainable evaluation framework is proposed in combination with the life cycle analysis and applied to a low carbon and high end industrial park (LCHE) in Beijing, China. Results show that the LCHE industrial park can contribute to both energy-saving and greenhouse gas emission mitigations compared with other industrial parks. In terms of economic performance, although the economic profits are considerable, the investment per constructed area is relatively high. The results of sustainable analysis of the LCHE industrial park can thus shed light on future upgrading of industrial parks.